Chronic Pain Physiopathology and Treatment - Vanaclocha, Vicente; Saiz-Sapena, Nieves (IntechOpen, 2021)
Chronic pain is a part of the human condition, despite immense advancements in pain treatment and management. In many societies, easy access to opioids has created a drug abuse crisis. Unfortunately, we seem to have forgotten many techniques that have been used in the past with great success. Some of these techniques continue to be useful, particularly in areas of the globe where resources are limited. This book attempts to remind those of us in the medical profession about the existence of some of these techniques and their ongoing utility. We need to master them or keep them in our armamentarium for the good of our patients.